Mechanical digit sensory stimulation: a randomized control trial on neurological and motor recovery in acute stroke - Zhang, Shuting; Yu, Yang; Xu, Panpan; Shen, Xianshan; Fang, Chuanqin; Wu, Xiaosan; Qu, Ping; Wu, Tingting; Wang, Qing Mei; Luo, Xun; Hong, Yongfeng (Frontiers in Neuroscience, 2023)
Background: Mechanical digit sensory stimulation (MDSS) is a novel therapy designed to accelerate the recovery of upper limb (including hand) function in patients with hemiplegia following a stroke. The primary goal of this study was to investigate the effect of MDSS on patients with acute ischemic stroke (AIS). Methods: Sixty-one inpatients with AIS were randomly divided into conventional rehabilitation group (RG) and stimulation group (SG), and the latter group received MDSS therapy. A healthy group consisting of 30 healthy adults was also included. The interleukin-17A (IL-17A), vascular endothelial growth factor A (VEGF-A), and tumor necrosis factor-alpha (TNF-α) plasma levels were measured in all subjects. The neurological and motor functions of patients were evaluated using the National Institutes of Health Stroke Scale (NIHSS), Mini-Mental State Examination (MMSE), Fugel-Meyer Assessment (FMA), and Modified Barthel Index (MBI). Results: After 12 days of intervention, the IL-17A, TNF-α, and NIHSS levels were significantly decreased, while the VEGF-A, MMSE, FMA, and MBI levels were significantly increased in both disease groups. No significant difference was observed between both disease groups after intervention. The levels of IL-17A and TNF-α were positively correlated with NIHSS but negatively correlated with MMSE, FMA and MBI. The VEGF-A levels were negatively correlated with NIHSS but positively correlated with MMSE, FMA and MBI. Conclusions: Both MDSS and conventional rehabilitation significantly reduce the production of IL-17A and TNF-α, increase the VEGF-A levels, and effectively improve cognition and motor function of hemiplegic patients with AIS, and the effects of MDSS and conventional rehabilitation are comparable.